The effect of recent legislation on the draft planning and development bill for the Western Cape - Ogle, Fiona Jane (Department of Public Law, 2021)
The object of urban planning is to improve the quality of life and the welfare of the community involved. However, planning policies and controls need to be embodied in legislation in order to make them applicable to the general public. Planning law has suffered from many shortcomings. It has reflected the racial bias of the past which has led to fragmented and unco-ordinated legislation. It reflects the previous Constitutional hierarchical allocation of powers which has resulted in centralised, "top down" planning with local authorities depending on Provincial government for delegated powers. It is control rather than development orientated. In order to provide a context for examining the effect of recent legislation on planning law, a brief summary of existing legislation will be set out.